Experimental and numerical study of the joinability of sheets by sheet-bulk forming - Bragança, Ivo (2019)
The authors present an innovative mechanical joining process that allows to connect perpendicular sheets to one another. This study is focused on joining similar and dissimilar sheets, based on sheet-bulk forming technology, and it is supported by experimental data and numerical simulation. Destructive tensile tests of different joined materials were performed to determine the maximum force that the joints are capable to withstand without failure. The joining technique should be chosen according to the materials joint combination. The two-stages technique could be a valid option to overcome the clearance between the plastically deformed polycarbonate tenon and aluminium mortise.